2010
DOI: 10.2176/nmc.50.291
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intraoperative Brain Shift Using an Ultrasound-Linked Navigation System for Brain Tumor Surgery

Abstract: Image-guided neurosurgery using navigation systems is an essential tool to increase accuracy in brain tumor surgery. However, brain shift during surgery has remained problematic. The present study evaluated the utility of a new ultrasound (US)-linked navigation system for brain tumor surgery in 64 patients with intracranial tumors. The navigation system consisted of a StealthStation TM navigation system, a SonoNav TM system, and a standard US scanner. This system determines the orientation of the US images and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 26 publications
2
50
0
Order By: Relevance
“…Another report described the magnitude of pyramidal tract displacement due to removal of tumor as varying from 0.5 to 8.7 mm on the lesion side and from 0 to 3.6 mm on the normal side [12]. Use of an ultrasound-linked navigation system or updating navigation with intraoperative images have been used to compensate for brain shift [13]. However, all these procedures are cumbersome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another report described the magnitude of pyramidal tract displacement due to removal of tumor as varying from 0.5 to 8.7 mm on the lesion side and from 0 to 3.6 mm on the normal side [12]. Use of an ultrasound-linked navigation system or updating navigation with intraoperative images have been used to compensate for brain shift [13]. However, all these procedures are cumbersome.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Ohue et al, reported inserting four silicone catheters at the tumor margin after dural incision. Following insertion of the catheters, ultrasound-linked navigation clearly demonstrated the location of the catheter as a real-time image [13]. However, the problem with this approach is that some tumors show only fair or poor ultrasound images, making residual tumor difficult to evaluate using a synchronized navigation system during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The navigation system was used in conjunction with an US scanner (Prosound SSD-5500 or alfa 7, ALOKA Co., Tokyo, Japan) for resection of the tumor [39]. After identifying that cortical MEPs could be recorded, brain shift was evaluated using an US image [39], and the accuracy of the fence-post technique was confirmed.…”
Section: Patientsmentioning
confidence: 99%
“…However, the accuracy of the navigation systems progressively decreases during surgical procedures, a phenomenon described as "brain shift" [39]. Although a re-registration technique using intraoperative magnetic resonance (MR) imaging is useful for resolving the problem of brain shift [42], intraoperative MR imaging techniques are limited by factors such as manpower, cost, and restricted surgical access, and surgeons must stop the operation for repeat intraoperative MR imaging [16,39]. Therefore, fence-post catheter techniques that use navigation systems have been used before beginning the resection of the glioma [16,39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation